An evaluation of the evolution of the gene structure of dystroglycan - Brancaccio, Andrea (BMC Res Notes, 2017)
BACKGROUND: Dystroglycan (DG) is an adhesion receptor complex composed of two non-covalently associated subunits, transcribed from a single gene. The extracellular α-DG is highly and heterogeneously glycosylated and binds with high affinity to laminins, and the transmembrane β-DG binds intracellular dystrophin. Multiple cellular functions have been proposed for DG, notwithstanding that its role in skeletal muscle appears central as demonstrated by both primary and secondary severe muscular dystrophic phenotypes collectively known as dystroglycanopathies. We recently analysed the molecular phylogeny of the DG core protein and identified the α/β interface, transmembrane and cytoplasmic domains of β-DG as the most conserved region. It was also identified that the IG2_MAT_NU region has been independently duplicated in multiple lineages. RESULTS: To understand the evolution of dystroglycan in more depth, we investigated dystroglycan gene structure in 35 species representative of the phyla in which dystroglycan has been identified (i.e., all metazoan phyla except Ctenophora). The gene structure of three exons and two introns is remarkably conserved. However, additional lineage-specific introns were identified, which interrupt the coding sequence at distinct points, were identified in multiple metazoan groups, most prominently in ecdysozoans. CONCLUSIONS: A coding DNA sequence (CDS) intron that interrupts the encoding of the IG1 domain is universally conserved and this intron is longer in gnathostomes (jawed vertebrates) than in other metazoans. Lineage-specific gain of additional introns has occurred notably in ecdysozoans, where multiple introns interrupt the large 3′ exon. More limited intron gain has also occurred in placozoa, cnidarians, urochordates and the DG paralogues of lamprey and teleost fish. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-016-2322-x) contains supplementary material, which is available to authorized users.